Ethnobotany of lalaban as a food source in the peri-urban Sundanese community of Cireundeu Hamlet, West Java, Indonesia - BUDI IRAWAN; DHEA SHINTA PRATITIS SIAGIAN; ANNISA ANNISA; ENENG NUNUZ ROHMATULLAYALY; MUHAMMAD IHSAN; SURYANA SURYANA; BUDIAWATI S. ISKANDAR; JOHAN ISKANDAR (Society for Indonesian Biodiversity, 2026)
Abstract. Irawan B, Siagian DSP, Annisa, Rohmatullayaly EN, Ihsan M, Suryana, Iskandar BS, Iskandar J. 2026. Ethnobotany of lalaban as a food source in the peri-urban Sundanese community of Cireundeu Hamlet, West Java, Indonesia. Biodiversitas 27 (3): d270328. https://doi.org/10.13057/biodiv/d270328. Local communities understand how to utilize the plants around them, passing down this traditional ecological knowledge (TEK) from their ancestors in utilizing surrounding plant resources, including fresh vegetables known as lalaban in Sundanese cuisine. This study documents and analyzes the diversity, utilization patterns, and cultural importance of lalaban among the peri-urban community of Cireundeu, Cimahi City, West Java, Indonesia. An ethnobotanical mixed-methods approach was employed through semi-structured interviews with 13 key informants, structured questionnaires with 56 respondents, participatory observation, and species identification using Plants of the World Online (POWO). One method they use these plants is in a vegetable salad called lalaban. Lalaban is common among the Sundanese people and is part of their daily diet. The community of Cireundeu Hamlet, Cimahi City, West Java, knows how to process and use lalaban. Currently, knowledge about lalaban is being lost due to globalization and large-scale deforestation. This study highlights the Cireundeu community's extensive knowledge of lalaban as a food ingredient. A total of 38 lalaban species belonging to 24 families were recorded, with Asteraceae as the most represented family. Leaves were the most utilized plant organ (51%), followed by fruits (16%), stems (14%), flowers (11%), and seeds (8%). Lalaban sources were primarily gardens (62%), forests (24%), home gardens (13%), and rice fields (1%). Relative Frequency of Citation (RFC) analysis indicated four culturally important species: Manihot esculenta and Carica papaya (RFC = 1), Pilea melastomoides (0.64), and Crassocephalum crepidioides (0.38). Lalaban consumption ranges from one to six days per week and reflects both nutritional and cultural significance, particularly cassava as a cultural keystone species. Documentation of this knowledge is essential to support conservation strategies, local food security, and intergenerational transmission of TEK amid peri-urban environmental change.